Exploration of Visual Aesthetics in Aerobics Sports (Journal of Global Arts Studies, 2024)
Background: With social development and the improvement of people’s living standards, aerobics, which combines both fitness and aesthetic characteristics, has become increasingly popular among the general public. Although research on aerobics has gradually expanded, studies focusing on its visual aesthetics remain relatively insufficient. Objective: This study aims to conduct an in-depth analysis of the visual aesthetic characteristics of aerobics, explore the forms of aesthetic expression in different styles of aerobics, and examine how optimizing visual elements can enhance its artistic expression and ornamental value. Methods: This study investigates the visual aesthetic characteristics of aerobics through theoretical analysis and comparative research methods. By comprehensively applying these approaches, the research seeks to construct a systematic analytical framework for the visual aesthetics of aerobics. Results: The findings indicate that the visual aesthetics of aerobics not only enhance the viewing value of the activity itself but also promote aesthetic communication between participants and audiences, thereby possessing important cultural value and social significance. Conclusion: Future studies on the visual aesthetics of aerobics should place greater emphasis on interdisciplinary integration and innovative approaches in order to adapt to evolving aesthetic demands and changing cultural contexts.
Keywords: Aerobics; Esthetics; Sports aesthetics; Visual Culture